An Analysis of Deixis in The Doraemon Comic - Putriarini Marta Kusuma; Vita Nurul Hidayah; Ani Susanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The goals of this study are to examine the various types of deixis and identify the most dominant deixis in the Doraemon comic. This study used descriptive qualitative content analysis to analyze deixis in the comic's selected chapter. According to the findings, there are three types of deixis found in comics: person deixis, spatial deixis, and temporal deixis. The deictic words of person deixis are he, it, they (the third person singular personal pronoun), I (the first person singular personal pronoun), your (possesive form of pronoun you), my (possessive form of pronoun I), and our (possessive form of pronoun we). The deictic words of the spatial deixis are that, this, these, those (demonstrative pronoun), and here, there (adverb of place). The deictic word of the temporal deixis is now (adverb of time). Furthermore, the most dominant deixis in the Doraemon comics are person deixis found 48 times, followed by spatial deixis are 11 times, and temporal deixis appear twice.